Differences obesity at subnational levels in Chile and the potential for targeted interventions. (30th September 2020) - Urquidi, C; Cumsille, F; Sepulveda, A; Garrido, M
Abstract: Background: Chile has a high prevalence of obesity (PO), and this has increased even more in recent years. Public health interventions have not impacted, probably because a geographic distribution of the cases at a lower level is unknown. We described the geographic distribution and change of obesity at a sub-regional level in Chile, and to identify targets areas/groups for interventions. Methods: We did a secondary analysis of the latest two National Health Surveys (2009, 2016), using Regions and Health Service (HS) levels, which are the second and third administrative division of Chile, respectively. HSs were the smallest geographical unit possible to analyze with this data. Logistic regression models were fit to test differences between sex, age, number of children, family income, educational level, regions, and HS, using the lowest value of each variable as the reference group, adjusting by sex and age. Results: At the national level, PO increased from 25% to 34% from 2009 to 2016. The southern regions have the highest PO in 2016 (Los Rios: 45%, Aysen:44%, Araucania:42%), and the lowest PO is even more than 30%. Although, the highest relative increase was in the north and central regions (Tarapacá:94%, Valparaíso:89%, Coquimbo:62%), as well as their HS. At HS level, in the Metropolitan Region, the PO varies from 21% to 46% in 2016 (OR = 3.3 IC95%1.4-7.9). Likewise, in the Valparaiso Region, it goes from 24% to 44% (OR = 2.9 IC95% 1.2-7). These differences in PO among HS levels in those regions were lower in 2009. Lower family income, educational level, and females with two or more children were associated with obesity in both surveys. Conclusions: There is a high prevalence and increases in obesity in Chile at national and sub-national levels. The large variability in obesity observed among regions and Health Services suggests that lower geographical areas would be a potential target for effective interventions, complementarity to those at national levels. Key messages: Analysis and intervention at a subnational level are required for preventing obesity in Chile. The high prevalence of obesity in Chile has a large variability among the subnational levels.